Evaluation of the detection techniques of toxigenic Aspergillus isolates - Darab, Yazdani; Mior Ahmad, Zainal Abidin; Tan, Yee How; Sijam, Kamaruzaman (Academic Journals, 2010)
Aflatoxins are difuranocoumarin derivatives produced by some Aspergillus species through a polyketide pathway. Mycotoxins are considered hazard ous and there is a need for accurate detection of each toxin. Several screening methods for direct visual determination of aflatoxins and ochratoxin A(OTA) production have been reported. These methods rely on using different types of coconut culture media, methylated β-cyclodextrin and ammonium hydroxide vapour tests. However, our results showed that use of these techniques were not sufficiently sensitive for all Aspergillus species and suggested a simple thin layer chromatography (TLC) as a sensitive and reliable technique for detection of aflatoxins and OTA produced by Aspergillus and Eurotium species.